1987
DOI: 10.1136/ard.46.10.787
|View full text |Cite
|
Sign up to set email alerts
|

Gold colitis induced by auranofin treatment of rheumatoid arthritis: case report and review of the literature.

Abstract: SUMMARY A case of ulcerative colitis occurred during treatment of rheumatoid arthritis with the new oral gold preparation auranofin after a cumulative dose of 2160 mg. A barium enema showed loss of mucosal pattern and a rectal biopsy disclosed deep erosions, mucosal inflammation, and crypt abscesses. Precipitates of gold were seen in the periglandular stroma. On electron microscopy the gold deposits seemed to be identical to granules described in gold nephropathy. As the extrapolated serum gold level was withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“… 15 Several cases of severe colitis due to gold therapy regardless of the route of administration have been reported; rare reports also describe colon perforation. 36 , 37 Although most cases occurred after many months of treatment, one report describes severe colitis occurring after 4 weeks of treatment with auranofin. 38 For this reason, we were unable to exclude auranofin as a possible cause of death in one patient who had intra-abdominal sepsis, and classified the adverse event as a suspected unexpected serious adverse reaction.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Several cases of severe colitis due to gold therapy regardless of the route of administration have been reported; rare reports also describe colon perforation. 36 , 37 Although most cases occurred after many months of treatment, one report describes severe colitis occurring after 4 weeks of treatment with auranofin. 38 For this reason, we were unable to exclude auranofin as a possible cause of death in one patient who had intra-abdominal sepsis, and classified the adverse event as a suspected unexpected serious adverse reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Parenteral gold typically causes side effects in about 35% of patients, which can include dermatitis, diarrhea, or stomatitis. More severe reactions such as nephritis, bone marrow suppression, colitis, and hepatotoxicity are more rarely observed [ 28 , 29 ]. While the toxicity profile for colloidal gold and GNPs does not demonstrate any hematologic or biochemical sequelae, these gold formulations are not currently used in the treatment of rheumatoid arthritis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…9, 47 Hematological abnormalities can also be sometimes produced by gold complexes and include eosinophilia, thrombocytopenia 9 and rarely aplastic anaemia probably as a result of a direct inhibition of myelopoiesis. 48 Several other reports have also mentioned the rare consequences of using gold complexes including entercolitis with bloody diarrhea, 49, 50 diffuse inflammatory lung reactions 51 and neurotoxicity. 52 Gold therapy is not recommended during pregnancy, 53 as animal studies have shown it to be teratogenic.…”
Section: Gold Toxicitymentioning
confidence: 99%